Training Across Boundaries. (April 2015) - Arulanandam, Sherlie; Macpherson, Rob
Summary: Background: This project arises from recent literature that has challenged a conventional view of training as being professional‐specific or 'silo' based. Various authors have recommended that to train psychiatrists for the future, it will be helpful to provide opportunities for exposure to different medical specialties, including general practice. Methodology: Training Across Boundaries (TAB) started in February 2013, aiming to develop training links between core psychiatry and medical specialties and primary care. The project encouraged the use of up to six sessions in a medical speciality or in primary care during a 6–month core psychiatry placement, and evaluated the benefits gained from this experience. Feedback was obtained from all the participants by means of structured interviews. To train psychiatrists it will be helpful to provide opportunities for exposure to different medical specialties Results: Results from the structured interviews with the participants are presented. Overall the project seems to have broadly achieved its aims, in the first year of activity. Discussion and conclusions: The pilot programme seems to have opened up opportunities for cooperation and learning between doctors from different disciplines. The experience of TAB has helped trainees to see many of the commonalities of practice, but also the cultural differences that operate in different parts of the health service. The results of the project show us that we need to think more about the potential value of bringing training in psychiatry, primary care and medical specialties closer, to improve the breadth and quality of training and patient care.